Finding a new direction for Indonesian democracy: analysis of limitations of the president's powers in the amendments to the constitution - Enny Agustina; Misnah Irvita; Saharuddin Saharuddin; Erman I Rahim; Mohamad Hidayat Muhtar (LEGAL BRIEF, 2024)
The purpose of this study is to investigate the rationale and consequences of the strategy of reducing executive authority, particularly that of the president, that was incorporated into the Republic of Indonesia Constitution of 1945 (UUD 1945) via a series of modifications. To comprehend the modifications to the constitution, this study employs a normative or doctrinal approach, concentrating on the analysis of pertinent papers, reports, and literature. According to the findings, these amendments were implemented in reaction to calls for reform and democratization. They sought to build a more balanced system of government with strong principles of checks and balances among the executive, legislative, and judiciary, and they eliminated the sacred and static views of the 1945 Constitution during the New Order era. This embodies the shift in Indonesian governance from a top-down, autocratic system to a bottom-up, democratic one, where checks and balances on the presidency are put in place to forestall any return to autocracy and guarantee greater citizen input into policymaking